Semantic classification of verbs in CROVALLEX - Mikelić Preradović, Nives (2010)
The paper describes the implementation of the Levin’s syntactic-semantic classification of English verbs onto verbs in Croatian language. The current Croatian valence verb lexicon (CROVALLEX) containing 1739 verbs associated with 5118 valence frames was enriched with 72 broad semantic classes with two further levels of subdivision (173 classes in total). The research results show that such classification helps in capturing the relation between the syntax and semantics of Croatian verbs in order to reduce the redundancy in the lexicon, but they also show that Levin's classification does not provide a means for full inference of the verb semantics on the basis of its syntactic behavior for Croatian language. The research brought us to conclusion that we need to introduce the more distinctive semantic roles.
Projekt MZOS
Projekt MZOS
ENG